PCSK9 inhibitors for treating hypercholesterolemia. (11th February 2020) - Pasta, Andrea; Cremonini, Anna Laura; Pisciotta, Livia; Buscaglia, Angelo; Porto, Italo; Barra, Fabio; Ferrero, Simone; Brunelli, Claudio; Rosa, Gian Marco
ABSTRACT: Introduction : Scientific evidence on subjects treated with statin or other lipid-lowering treatments has established that treatments aiming to lower low-density lipoprotein cholesterol (LDL-C) can reduce atherosclerosis. PCSK9 inhibitors (PCSK9-i), thanks to their efficacy in reducing LDL-C constitute a further step in the treatment of dyslipidemia and cardiovascular (CV) diseases. Areas covered : The purpose of this narrative review is to summarize the current knowledge of PCSK9-i, with particular regard to pharmacodynamic, pharmacokinetic, and clinical data on evolocumab and alirocumab. Expert opinion : PCSK9-I are effective in reducing atherosclerotic events through their significant LDL-C-lowering action similarly to statins. Furthermore, these drugs can be considered safe and well-tolerated. However, some controversies remain with regard to their efficacy in reducing mortality and the paucity of data on both pleiotropic effects and long-term safety of these drugs. However, future studies will focus on understanding the effects of very low cholesterol levels on health. At present, we know that the genetic model of PCSK9 deficiency is characterized by very low LDL-C levels without particular health problems. Yet, we do not know the effect of prolonged PCSK9 inhibition induced by antibody action during the lifetime of normal subjects.